PR and Marketing techniques required for the hospitality and luxury apparel industry - Ranka, Divya (ATLAS SkillTech University, 2025)
This summer internship report, "An Insightful Exploration: Branding and PR in the F&B Industry and the Apparel Industry," reflects an overall view of my enriching experience at CARPEDIEM, which is a pioneering branding and PR agency. The objective of this report is to put into a nutshell the great insights and practical learning through this internship program that I undertook during the summer as part of my second-year MBA curriculum at Atlas Skilltech University. Through continuous active participation in almost all promotional plans, strategizing, target identification, and influencer management, I got to be a part of the dynamic world of Branding and PR under the guidance of the highly esteemed faculty mentor DR Mukul Bhatt. The following summary aims to provide an overview to the reader regarding the detailed findings and reflections shared in the latter part of this report, which will enable him to understand the worth of this transformative internship experience at CARPEDIEM.
Project Report on PR and Marketing techniques required for the hospitality and luxury apparel industry (2023-2025) Under the Guidance of Prof. Mukul Bhatt
Keywords: Branding; PR; Apparel Industry; CARPEDIEM; strategizing; influencer management; target identification; Exploration